Specimen preparation for Serial-Block Face Scanning Electron Microscopy and Contrast Evaluation by Transmission Electron Microscopy - Baumann, Dominik (Jihočeská univerzita, 2018)
Lanthanide salts were tested as alternative heavy metal stains to uranyl acetate for the sample preparation for serial block-face scanning electron microscopy. The influences of section thickness and the application of microwave radiation during sample preparation on the contrast of sections in transmission electron microscopy were also examined.
Specimen preparation for Serial-Block Face Scanning Electron Microscopy and Contrast Evaluation by Transmission Electron Microscopy
Keywords: electron microscopy